THE RELATIONSHIP OF TEACHER AND STUDENT EDUCATIVE INTERACTIONS ON CHEMISTRY LEARNING ACHIEVEMENT OF SMAN 4 MATARAM STUDENTS - Soumi, Riri Sahri; Hakim, Aliefman; Andayani, Yayuk (UIN Mataram, 2023)
This study aims to determine how the educative interaction of teachers and students and their relationship to chemistry learning achievement of grade XI and XII IPA students of SMAN 4 Mataram. This research is an ex-post facto quantitative study with a total population of 275 students in class XI and XII IPA. The sample used was 163 students who were determined using a stratified random sampling technique. The data collection method uses a teacher-student educational interaction questionnaire and documentation of the results of the Mid Semester Examination scores for the chemistry subject for Odd Semester 2022/2023 Academic Year. Descriptive analysis technique to find out how the pattern of teacher-student educational interaction and chemistry learning achievement as well as hypothesis testing with Pearson Product Moment correlation. Based on the descriptive analysis, the percentage of each indicator of the form of educational interaction states that students in class XI and XII IPA in chemistry learning use two-way communication. The percentage of educational interaction based on strata (class) and overall the students of SMAN 4 Mataram are in the moderate category. The results of the study stated that there was a positive and significant relationship between the educative interaction of teachers and students on the chemistry learning achievements of class XI and XII IPA SMAN 4 Mataram in the 2022/2023 Academic Year. The strength of the relationship between the educational interaction variable and the chemistry learning achievement is included in the high category with each addition of 1.289 the value of the chemistry learning achievement, the value of the educational interaction increases by 34,75%.